PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI PADA MATERI PENGOLAHAN ANGKA UNTUK SISWA KELAS 7 SMP - Mahadir Muhamad Erfin Abdilah; Dyah Lestari; Baskoro Arif Widodo (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study began with students who had difficulty in understanding and remembering formulas in Microsoft Excel, this caused students to feel bored and less enthusiastic in learning formulas using guidebooks, even though students were allowed to bring cell phones to school. The study was conducted to develop learning media on number processing material that has validity, practicality, and effectiveness in learning. The ADDIE model in Research and Development (R&D) was used as a method using questionnaires and questionnaires for data collection. The trial subjects involved 15 7th grade students of SMPN 23 Malang. The validation results by material and media experts showed a very high level of feasibility with scores of 97.5% each for material validation and 100% for media validation. The practicality of the media was shown from the student's response that the media was very feasible with a score of 85.33%. The effectiveness of the media was seen from the N-Gain value which showed an influence of 0.657 in the moderate category and an increase in student learning outcomes from an average score of 51.55 to an average score of 83.33. Thus, the developed learning media is proven to be very feasible, practical, and effective in improving students' understanding of number processing material. Follow-up of this research can be done with wider trials and the development of more interactive media features.